Serological analysis of antigen-specific helper factors specific for poly-L(Tyr, Glu)-poly-DLAla--poly-LLys [(T, G)-A--L] and L Glu60-LAla30-LTyr10 (GAT). - Howie, S; Parish, C; David, C; McKenzie, I; Maurer, P; Feldmann, M (1979)
In vitro prepared antigen-specific helper factors reactive to the synthetic polypeptide antigens poly-L(Tyr, Glu)-poly-DLAla--poly-LLys [(T, G)-A--L] or LGlu60-LAla30-LTyr10 (GAT) and bearing Ia determinants were analyzed serologically to determine the nature of the Ia determinants they expressed. I subregion-specific mouse anti-Ia antisera were used, and showed that (T, G)-A--L-specific helper factor (HF) contains I-A subregion-controlled determinants, whereas GAT-specific HF carries I-J subregion-controlled antigens. This unexptected finding was confirmed in both the H-2k and H-2 b haplotypes, using a variety of anti-I-J antisera. Rabbit anti-Ia antisera also reacted with both HF which raised the possibility that the Ia determinants on HF may be carbohydrate in nature. The fact that HF has a low molecular weight and yet contains Ia determinants, antigen-binding capacity and idiotypic markers is compatible with this interpretation.